Hemispheric asymmetry of ipsilateral motor cortex activation during unimanual motor tasks: further evidence for motor dominance - Ziemann, Ulf; Hallett, Mark (Clinical neurophysiology, 2001)
Objectives: To test to which extent the increase in ipsilateral motor cortex excitability during unimanual motor tasks shows hemispheric asymmetry. Methods: Six right-handed healthy subjects performed one of several motor tasks of different complexity (including rest) with one hand (task hand) while the other hand (non-task hand) was relaxed. Focal transcranial magnetic stimulation was applied to the motor cortex ipsilateral to the task hand and the amplitude of the motor evoked potential (MEP) in the non-task hand was measured. In one session, the task hand was the right hand, in the other session it was the left hand. The effects of motor task and side of the task hand were analyzed. Spinal motoneuron excitability was assessed using F-wave measurements. Results: Motor tasks, in particular complex finger sequences, resulted in an increase in MEP amplitude in the non-task hand. This increase was significantly less when the right hand rather than the left hand was the task hand. This difference was seen only in muscles homologous to primary task muscles. The asymmetry could not be explained by changes in F-wave amplitudes. Conclusions: Hemispheric asymmetry of ipsilateral motor cortex activation either supports the idea that, in right handers, the left motor cortex is more active in ipsilateral hand movements, or alternatively, that the left motor cortex exerts more effective inhibitory control over the right motor cortex than vice versa. We suggest that hemispheric asymmetry of ipsilateral motor cortex activation is one property of motor dominance of the left motor cortex.